La luz azul emitida por pantallas y su incidencia en la fatiga visual en niños de 7 a 10 años en la parroquia san juan, cantón Puebloviejo, periodo septiembre 2017 a febrero 2018. - Quinto Mora, Marcia Roxana ;Nancy Inocencia Ledesma Diéguez (2018)
The present work is directed to the study of visual fatigue in children from 7 to 10 years old in the San Juan parish of the Puebloviejo canton, due to the excessive use they make of technological devices with blue screens. First of all it is important to highlight that this type of screens are found in computers, tablets, smart phones, video games, among others. One of the factors that intervenes in that said screens have a harmful effect, is the little distance that is conserved between the screen and the user, impacting directly on the eye. In general, children who make use of this type of artifact have no control over the time spent on this, which is why the time of exposure to these screens is usually prolonged, combined with the short distance to which it is used. certain consequences at a visual level. In this case, emphasis will be placed on the visual fatigue that some of the children may have. For this reason we went to the school in order to provide a completely free visual examination and a survey to assess trends in the use of devices with LED screens. It was found that most of the children presented made frequent use of any device, whether computers, tablets, smart phones and video games, also that the results show that more than 50% of the representative sample of the students of the school November 17, They manifest having the symptoms of visual fatigue. In view of such problems, the use of these devices should be regulated and, in case of having visual fatigue, the use of GX7 antiglare lenses is recommended.